Ultrastructure of a Columbite-Tantalite Mineral from the Zhaojinggou Ta-Nb Deposit in the North China Craton: Direct Evidence of the Formation Mechanism of the Columbite-Group Minerals. (3rd December 2022) - Zuo, Yushan; Gao, Zhengxi; Zuo, Lei; Zhang, Peng; Liu, Rui; Zhang, Qing; Zhang, Tingting
Abstract : The formation of columbite-group mineral phases in peraluminous granite has not been demonstrated to date. Here, a nanoscale study of the columbite-tantalite mineral in the Zhaojinggou Nb-Ta deposit in North China Craton elucidated its formation mechanism and the role of fluids in Nb-Ta mineralization. Transmission electron microscopy (TEM) analysis of a focused ion beam cut of the columbite-tantalite mineral revealed a comparatively well-ordered mineral structure. Energy-dispersive X-ray spectroscopy (EDS) revealed the presence of Nb, Ta, Mn, W, Fe, Sn, and Pb in the columbite-tantalite mineral. Furthermore, detailed TEM images depicted the nanoscale hydrothermal fluid occurring within the columbite-group mineral grain as well as between columbite-tantalite mineral and quartz grains. K, Al, Si, and O were found to be enriched in the hydrothermal fluid that was present between the quartz grains and the columbite-tantalite mineral. It did not react with the mineral grains of the columbite group. The ultrastructure of the columbite-tantalite mineral suggested the columbite-group mineral in the Zhaojinggou Nb-Ta deposit formed during magmatic crystallization rather than from hydrothermal fluids. Furthermore, HR-TEM images provided the first nanoscale observations of the fluid-mediated mineral dissolution and amorphous phase formation. This study also revealed that the mineral dissolution, element transport, and reprecipitation were significantly influenced by the fluid amorphous phase in the Nb-Ta deposits.